2012
DOI: 10.1007/s00424-012-1088-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C delta contributes to increase in EP3 agonist-induced contraction in mesenteric arteries from type 2 diabetic Goto-Kakizaki rats

Abstract: Prostaglandin E(2) (PGE(2)), an important and ubiquitously present vasoactive eicosanoid, may either constrict or dilate systemic vascular beds. However, little is known about the vascular contractile responsiveness to and signaling pathways for PGE(2) at the chronic stage of type 2 diabetes. We hypothesized that PGE(2)-induced arterial contraction is augmented in type 2 diabetic Goto-Kakizaki (GK) rats via the protein kinase Cδ (PKCδ) pathway. Here, we investigated the vasoconstrictor effects of PGE(2) and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
1
17
0
2
Order By: Relevance
“…Increased formation of vasoconstrictors and altered effectiveness of vasodilators may underlie such impairments. PGE 2 has been demonstrated to function primarily as a vasodilator and vasodepressor when intravenously infused into many species, including humans, dogs, rabbits, mice and rats; however, in certain physiologic settings PGE 2 acts as a vasoconstrictor [12, 16, 17, 3843]. Our studies indicate that in the presence of Ang II, PGE 2 exhibits vasoconstrictor effects in mouse femoral arteries.…”
Section: Discussionmentioning
confidence: 66%
“…Increased formation of vasoconstrictors and altered effectiveness of vasodilators may underlie such impairments. PGE 2 has been demonstrated to function primarily as a vasodilator and vasodepressor when intravenously infused into many species, including humans, dogs, rabbits, mice and rats; however, in certain physiologic settings PGE 2 acts as a vasoconstrictor [12, 16, 17, 3843]. Our studies indicate that in the presence of Ang II, PGE 2 exhibits vasoconstrictor effects in mouse femoral arteries.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, previous studies demonstrated that PKCδ located in smooth muscle directly mediate vasocontractile effects. 54;55;57 Although PKC isoforms have been implicated in contractile responses in dispersed/cultured smooth muscle cells, 58;59 we believe this to be the first instance in which individual PKC isoforms have been specifically identified as being involved in a contractile response in intact vessels, at least when challenged with PDBu. Indeed, the present finding that rottlerin a selective PKCδ inhibitor abrogated hypertension observed in hyperandrogenic rats, indicates a causative role of the heightened PKCδ-mediated signaling in the pathogenesis of androgen-induced hypertension.…”
Section: Discussionmentioning
confidence: 87%
“…[8][9][10][11][12][13][14][15][16]27,28) Plasma samples were stored at −20°C until analysis. Briefly, plasma glucose, cholesterol, high-density lipoprotein (HDL) cholesterol, triglyceride, and serum non-esterified fatty acid (NEFA) levels were each determined with a commercially available enzyme kit (Wako Pure Chemical Industries, Ltd., Osaka, Japan).…”
Section: Ca Mo and Rv Treatmentsmentioning
confidence: 99%
“…The endothelium plays a central role in physiological maintenance of the vascular function by regulating vascular tone, leukocyte adhesion, and platelet activation, as a result of the release of vasoactive substances such as nitric oxide (NO), prostacyclin, and thromboxane A 2 (TXA 2 ). 1,[6][7][8][9][10][11][12][13][14][15][16] Several natural polyphenols have been evaluated for their ability to protect against endothelial dysfunction and, thus, for their effectiveness in preventing cardiovascular disease. 17) Indeed, we have also shown that long-term chlorogenic acid (CA) treatment (2 months) can normalize the impaired endothelium-dependent relaxation seen in diabetic rats.…”
mentioning
confidence: 99%